Leadership with a Purpose: Nine Case Studies of Schools in Tasmania and Victoria Where the Principal Had Undertaken the Principals as Literacy Leaders (PALL) Program. Issue 2 (3rd April 2018) - Townsend, Tony; Bayetto, Anne; Dempster, Neil; Johnson, Greer; Stevens, Elizabeth
ABSTRACT: This paper reports on Australian case study research in schools where principals completed the Principals as Literacy Leaders (PALL) program. The purpose was to gather data about the effects of PALL on principalsd' leadership and the impact of interventions in Reading on teaching, student learning, and achievement. Data gathering included interviews with principals, leadership teams and teachers (parents in some schools), a student survey and examples, and reading progress data. Findings indicated that PALL had impacted positively on principals' leadership and provided a framework to lead their teachers in ways that improved teaching practice, student engagement and learning.